SYSTEMATIZATION OF NURSING CARE FOR RENAL TRANSPLANT PATIENTS - Dayane Martins Souza, Dávila; Salles Silva de Oliveira, Ingryde; Paiva dos Santos, Silvânia; Guilherme Pereira, Victor; Corrêa Monteiro, Sylmara; Cristina Santos Alves, Elaine; de Freitas Moreira, Kerolaine; Marques Batista da Rocha, Rodrigo; Cristina Higino Passos, Flávia; Rocha Matos, Eliseu; Kelly Cardoso Silva, Jany; de Fátima Fernandes Santos, Maria; et al. (Health and Society, 2024)
Objective: to describe nursing care in the postoperative period of kidney transplantation. Methodology: an integrative literature review study was conducted. The search was conducted at the Virtual Health Library (VHL), Latin American and Caribbean Literature on Health Sciences (LILACS) and Scientific Electronic Library Online (Scielo) with the following descriptors: “kidney transplantation”, “nursing team”, “nursing care”. Results: nursing care for renal transplant patients involves technical and psychosocial aspects, requiring knowledge and experience in the application of the nursing process and systematization of nursing care. Conclusion: nursing needs to appropriate the profession’s own instruments, such as the systematization of nursing care and the nursing process, for the competent and timely offer of nursing care to transplanted patients.